Meister Eckhart’s Self-translations into the Vernacular - Vinzent, Markus (Bulletin de Philosophie Médiévale, 2017)
Abstract The present article presents a new manuscript discovery of an Eckhart manuscript hitherto thought to have been lost. The text section of Eckhartian texts consist to a large extent of questions, two of which are being discussed here. As it seems these texts are not, as previously believed, vernacular translations of Eckhart’s Latin exegetical commentaries, but of Latin questions which Eckhart seems to have collected in his Liber quaestionum and translated into the vernacular. ‘Eckhart’ here is taken as a broad label that may encompass Eckhart himself as well as his early readers.